Foliar optical traits indicate that sealed planting conditions negatively affect urban tree health. (December 2018) - Yu, Kang; Van Geel, Maarten; Ceulemans, Tobias; Geerts, Willem; Ramos, Miguel Marcos; Sousa, Nadine; Castro, Paula M.L.; Kastendeuch, Pierre; Najjar, Georges; Ameglio, Thierry; Ngao, Jérôme; Saudreau, Marc; et al.
Highlights: Soil sealing has a large impact on leaf functional trait variations of urban trees. Trees planted in highly sealed soils have low specific leaf area and water content. Optical traits explain the variations in functional traits due to soil sealing. Temporal variations in leaf optical traits reveal tree phenology change. Abstract: Urban trees play a key role in mitigating environmental problems in cities, but they often face harsh environmental conditions as they generally grow in sealed soils that have small rooting space and low water availability. In this context, rapid monitoring and assessment of tree health status is critical to maintain urban trees and secure the provisioning of urban ecosystem services. Across three European cities we selected 187 Tilia tomentosa trees growing under following planting conditions: (i) sealed, trees planted in small soil pits or strips surrounded by highly sealed surfaces (concrete, pavement or asphalt); and (ii) unsealed, trees planted in roomy soil surfaces (e.g. parks). We measured leaf reflectance and fluorescence and derived a set of optical traits from the measurements. We examined whether these non-destructively measured optical traits differ between planting conditions and whether they correlate with leaf functional traits, e.g. specific leaf area (SLA), leaf water content (LWC) and leaf water per area (LWA). Compared to the unsealed trees, sealed trees showed decreased SLA and LWC while increased LWA. Leaf optical traits differed between the unsealed and sealed trees. Highly sealed soils accelerated leaf senescence of the sealed trees compared to the unsealed trees, embodied in the temporal trend of optical traits. Sealed planting conditions negatively affect urban tree health status and phenology. These negative effects can be estimated by leaf optical traits, demonstrating the great potential of optical traits in assessing tree health status. Our findings provide insights into facilitating urban green management using optical traits and remote sensing data.